The utility of e-government public services for China’s information-disadvantaged groups - Chen, Yushi (2025)
Every citizen is an important stakeholder in the e-government system, and their willingness to adopt e-government, as well as their information literacy and skills, is crucial. In China, the rapid development of e-government has become a symbol of social progress. However, this positive initiative by the Chinese government has also exacerbated the plight of the information-disadvantaged groups in the current digital environment. These people live in rural areas, are older, less educated, have lower incomes, and are unable to own or use electronic devices to access e-government public services, thus affecting their survival and development. This study aims to analyse the particularities of e-government public service adoption among the information-disadvantaged groups in China. It further analyses how the digital divide, one of the significant barriers to implementing e-government systems, has affected the adoption of e-government public services by the information-disadvantaged groups. Ultimately, the study proposes potentially viable new models of e-government public services through existing practicable emerging technologies through a complete literature review and compendium.